On the role of non-shared environment for executive functioning in ADHD: A twin-differences design study - Willfors, C.; Poltrago, L.; Berggren, S.; Coco, C.; Anckarsäter, H.; Lichtenstein, P.; Ronald, A.; Bölte, Sven (2014)
Introduction: The study of differences between monozygotic (MZ) twin pairs with respect to ADHD may provide novel leads to disentangle the environmental contribution driving its phenotypes. Objectives: To examine non-shared environmental influences on executive function in dimensionally defined ADHD. Methods: This study included 27 MZ twin pairs (7 female) aged 11-20 years being moderately to substantially discordant for ADHD traits as assessed by the Attention Problem (AP) scale of the Child Behavior Checklist/Adult Behavior Checklist. The twins completed the Wisconsin Card Sorting Test (WCST) for cognitive flexibility and the Tower Test (TT) for foresighted planning. Two statistical approaches were used to analyze the data. First, correlations between ADHD trait intra-pair differences and WCST and TT scores were calculated. Second, the significance of those intra-pair differences on WCST and TT, using ADHD as categorical variable in clinically discordant pairs, was tested. Results: Both analysing strategies revealed a link between ADHD on one hand, and foresighted planning and inhibitory control on the other hand mediated by non-shared environmental factors. The first statistical approach yielded positive correlations between intra-pairs differences on the AP scale and intra-pair differences on two subscales of the TT: total rule violation (r s =0.41) and rule-violation-per-item-ratio (r s =0.38). Findings in categorically discordant pairs were consistent, showing within-pair differences on the same subtests (z-1.63, P=0.05, one-tailed and z=-1.60, P=0.05, one-tailed). Conclusions: Findings confirm previous research suggesting ADHD to be a quantitative extreme on a continuum with executive functions being a cognitive marker of ADHD traits. Non-shared environmental factors appear to influence planning skills and inhibitory control.